In-vivo treatment accuracy analysis of active motion-compensated liver SBRT through registration of plan dose to post-therapeutic MRI-morphologic alterations. (May 2019) - Boda-Heggemann, Judit; Jahnke, Anika; Chan, Mark K.H.; Ernst, Floris; Ghaderi, Ardekani Leila; Attenberger, Ulrike; Hunold, Peter; Schäfer, Jost Philipp; Wurster, Stefan; Rades, Dirk; Hildebrandt, Guido; Lohr, Frank; et al.
Highlights: First-time presentation of a method for in-vivo -accuracy analysis of dose-delivery with active motion-management (gating/tracking), which can serve as a benchmarking-tool for other treatment techniques. IVA is based on registration of post-radiotherapeutic MRI-morphologic-alterations to the corresponding isodose-structures of gantry-based/robotic SBRT-plans and structure analysis regarding volumes, surface-distance, conformity metrics and center-of-mass-differences. Liver-SBRT with active motion-management has shown median deviations <5 mm of planned dose and MR-morphologic alterations. Abstract: Background/purpose: In-vivo -accuracy analysis (IVA) of dose-delivery with active motion-management (gating/tracking) was performed based on registration of post-radiotherapeutic MRI-morphologic-alterations (MMA) to the corresponding dose-distributions of gantry-based/robotic SBRT-plans. Methods: Forty targets in two patient cohorts were evaluated: (1) gantry-based SBRT (deep-inspiratory breath-hold-gating; GS) and (2) robotic SBRT (online fiducial-tracking; RS). The planning-CT was deformably registered to the first post-treatment contrast-enhanced T1-weighted MRI. An isodose-structure cropped to the liver (ISL) and corresponding to the contoured MMA was created. Structure and statistical analysis regarding volumes, surface-distance, conformity metrics and center-of-mass-differences (CoMD) was performed. Results: Liver volume-reduction was −43.1 ± 148.2 cc post-RS and −55.8 ± 174.3 cc post-GS. The mean surface-distance between MMA and ISL was 2.3 ± 0.8 mm (RS) and 2.8 ± 1.1 mm (GS). ISL and MMA volumes diverged by 5.1 ± 23.3 cc (RS) and 16.5 ± 34.1 cc (GS); the median conformity index of both structures was 0.83 (RS) and 0.80 (GS). The average relative directional errors were ≤0.7 mm (RS) and ≤0.3 mm (GS); the median absolute 3D-CoMD was 3.8 mm (RS) and 4.2 mm (GS) without statistically significant differences between the two techniques. Factors influencing the IVA included GTV and PTV ( p = 0.041 and p = 0.020). Four local relapses occurred without correlation to IVA. Conclusions: For the first time a method for IVA was presented, which can serve as a benchmarking-tool for other treatment techniques. Both techniques have shown median deviations <5 mm of planned dose and MMA. However, IVA also revealed treatments with errors ≥5 mm, suggesting a necessity for patient-specific safety-margins. Nevertheless, the treatment accuracy of well-performed active motion-compensated liver SBRT seems not to be a driving factor for local treatment failure.